(untitled) (Research, Society and Development, 2022)
The bird’s gastrointestinal tract has a microbiological diversity, beneficial bacteria play a role in digestion and absorption, contribute to the immune system and competition against pathogens that make up approximately 10% of the intestinal microbiota. The most abundant phylum are Actinobacteria, Firmicutes, Fusobacteria and Bacteriodetes, such microorganisms are essential for bird health. The pathogenic microorganisms are Proteobacteria, Protozoa, Apicomplexa, Tenericutes and Firmicutes, colonize the lumen of the bird’s gastrointestinal tract without causing damage, however, when there is dysbiosis the pathogens multiply causing lesions in the intestinal mucosa and can cause enteric disorders, sometimes irreversible. The beneficial microbiota is able to stimulate the immune system with the production of T cells, decreasing the inflammatory process and the production of immunoglobulin A, G and M. Bifidobacterium influence the proliferation of macrophages, enhancing the animal’s immune system, in addition to producing bacteriocins which inhibits the multiplication of pathogens (Salmonella spp. and Clostridium perfringens). Lactobacillus spp. stimulate the secretion of immunoglobulins, lactate and acetate and inhibit the adhesion of pathogens to the intestinal epithelium. Bacteroides spp. and Bifidobacterium spp. they institute volatile fatty acids and suppress the toxicity of Salmonella spp., Escherichia coli and Campylobacter spp. The Bacteroides fragilis species stimulates the production of T cells in order to reduce inflammation. The main objective is to review the available scientific information about the intestinal microbiome of birds and its importance, detailing its composition and correlation with the immune system.